IDENTIFIKASI TIPOLOGI DESTINASI WISATA DAN STRATEGI PENGEMBANGANNYA SEBAGAI UPAYA MEWUJUDKAN PARIWISATA KABUPATEN KARANGASEM BERBASIS WISATA KONSERVASI - Wyana Lokantara, I Gede (Proceeding SENDI_U, 2017)
Karangasem regency is one of nine districts in Bali, which has tourism potential and can be developed into an attractive destination. But now the development of tourism destinations in the district is still not optimal so that requires a strategy in its development efforts. The purpose of this research is to identify the potential of tourism in Karangasem Regency by making the analysis of class / level and identify the cluster of tourist destinations based on the type of tourism, the availability of facilities and facilities and tourist visits, and make the development through SWOT cluster analysis which in the future can be a reference In developing conservation based tourism area in Karangasem regency. The method used is a mix method that combines qualitative and quantitative research analysis. The results of this research is the class / order of tourism destinations in karangasem district shows that the level of development of the destination is still in the middle to lower level, the number of indicators that have not been met make the pattern of development is still in the order of 3-6. Based on the survey results there are clusters of tourist destinations in Karangasem regency consisting of: nature tourism (nature) & beach (coastal), heritage tourism, and agro. Based on the above, it is necessary to make efforts and strategies to develop tourism destinations in Karangasem Regency such as tourism product development strategy based on tourism and conservation tourism, technology utilization in promotion strategy, tourism product strengthening and human resources quality improvement strategy for tourism management in Karangasem regency. Kata Kunci: Cluster of Tourism, conservation based tourism, tourism product.